Situation Report: Czechoslovakia, 7 August 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Harsh Sentence for Rudolf Battek Semiannual Report on Economic Development Designers Quit Designing The Building Trade: A Study in Failure